A Case of an Elderly Woman Who Developed Corneal Perforation in the Clinical Course of Myeloperoxidase Positive Antineutrophil Cytoplasmic Antibody-Associated Vasculitis - Shuhei Kobayashi; Makoto Harada; Aiko Yamada; Yasuhiro Iesato; Koji Hashimoto; Yuji Kamijo (Case Reports in Rheumatology)
Antineutrophil cytoplasmic antibody- (ANCA-) associated vasculitis (AAV) is a systemic vasculitis characterized by ANCA positivity and categorized into three main types: microscopic polyangiitis, granulomatosis with polyangiitis, and eosinophilic granulomatous with polyangiitis. Although AAV leads to systemic organ injury, such as of the lungs, kidneys, nerves, and skin, patients with AAV sometimes develop ocular lesions. Here, we report the case of an elderly woman who had been treated for AAV for seven years. She developed scleritis and relapsed twice, with elevation of serum disease markers such as ANCA titer and C-reactive protein. After the decline of these markers due to treatment with additional medication, her scleritis relapsed again and caused a corneal ulcer, which resulted in perforation without obvious marker elevation. She did not present with any symptoms of organ injury, except for ocular lesions. She was treated with surgery, followed by methylprednisolone and rituximab therapy. Subsequently, her ocular lesions and symptoms improved, and she did not relapse. AAV can cause various ocular manifestations. Although C-reactive protein and ANCA titers are useful markers of disease activity and the relapse of AAV complications, including ocular lesions, these markers do not always increase at the time of worsening ocular lesions. Therefore, it is important for clinicians treating patients with AAV to pay careful attention to serum data and physical findings, including the eyes.